2020
DOI: 10.1021/acs.langmuir.9b02942
|View full text |Cite
|
Sign up to set email alerts
|

A Lipid Photoswitch Controls Fluidity in Supported Bilayer Membranes

Abstract: Supported lipid bilayer (SLB) membranes are key elements to mimic membrane interfaces on a planar surface. Here, we demonstrate that azobenzene photolipids (azo-PC) form fluid, homogeneous SLBs. Diffusion properties of azo-PC within SLBs were probed by fluorescence microscopy and fluorescence recovery after photobleaching. At ambient conditions, we find that the trans-to-cis isomerization causes an increase of the diffusion constant by a factor of two. Simultaneous excitation with two wavelengths and variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 37 publications
4
64
0
1
Order By: Relevance
“… 27 Photoswitchable lipids have yielded optical control of several biological targets, including ion channels, 28 30 G-protein-coupled receptors (GPCRs), 31 33 enzymes, 34 , 35 nuclear hormone receptors, 36 38 immune receptors, 39 , 40 as well as membrane properties. 41 46 Among the photolipids developed to date several are analogues of lipids implicated in PA metabolism, which include fatty acids ( FAAzo4 ), 28 diacylglycerol ( PhoDAG and OptoDArG ), 29 , 34 lysophosphatidic acid ( AzoLPA ), 33 and phosphatidylcholine ( AzoPC ) 44 ( Figure 1 A,B).…”
Section: Introductionmentioning
confidence: 99%
“… 27 Photoswitchable lipids have yielded optical control of several biological targets, including ion channels, 28 30 G-protein-coupled receptors (GPCRs), 31 33 enzymes, 34 , 35 nuclear hormone receptors, 36 38 immune receptors, 39 , 40 as well as membrane properties. 41 46 Among the photolipids developed to date several are analogues of lipids implicated in PA metabolism, which include fatty acids ( FAAzo4 ), 28 diacylglycerol ( PhoDAG and OptoDArG ), 29 , 34 lysophosphatidic acid ( AzoLPA ), 33 and phosphatidylcholine ( AzoPC ) 44 ( Figure 1 A,B).…”
Section: Introductionmentioning
confidence: 99%
“…Together, the Nickel, Trauner and Lohmüller groups demonstrated the reversible tuning of membrane fluidity in supported lipid bilayers solely composed of AzoPC [11] . This study demonstrated that the activation energy for photolipid diffusion depends on the molecular interactions and aggregate formation.…”
Section: Membranesmentioning
confidence: 71%
“…Size and shape of the GUVs can be controlled by the lipid composition [7] . Incorporating photoswitchable lipids into GUVs allowed for the reversible control of membrane fission, [8] shape changes, [9] vesicle size, [10] bilayer fluidity, [11] bending rigidity, [8] domain formation and lipid‐lipid interactions [12] . GUVs can be manipulated, often irreversibly, by changing pH and temperature.…”
Section: Membranesmentioning
confidence: 99%
“…The plotted data contains the information required to calculate lateral diffusion coefficients, which are in turn used in membrane dynamics study. FRAP has been applied for comparative study of new types of liposomes [21][22][23], fluidity of the lipid bilayers [24,25] and proteins' dynamics in the membrane [26,27]. The main limitations of FRAP are photoswitching of analyte chemical or structural analytes and localised heating by the laser [28] which can change the sample.…”
Section: Fluorescence Of Membrane-bound Peptidesmentioning
confidence: 99%